2017
DOI: 10.5604/16652681.1226821
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Predicts Reduced Survival in Patients with Hepatocellular Carcinoma at First Diagnosis

Abstract: This retrospective study shows high prevalence of sarcopenia among cirrhotic patients with hepatocellular carcinoma. Presence of sarcopenia was identified as independent predictor of reduced overall survival. As easily measurable by CT, sarcopenia should be determined for prognostic purposes in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 33 publications
3
44
0
2
Order By: Relevance
“…This observation confirms the warning that sarcopenia is not exclusively to be sought in patients with low BMI, strengthening the importance and prevalence of sarcopenic obesity. 10,11,15 Our data further contributes to the definition of the role of sarcopenia as a possible predictor of reduced survival and cancer treatment toxicity, as has been previously shown in other oncological settings. 10 Accurate measurement tools are also needed in HCC, and CTbased technologies provide measurable and repeatable muscle mass measurement.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This observation confirms the warning that sarcopenia is not exclusively to be sought in patients with low BMI, strengthening the importance and prevalence of sarcopenic obesity. 10,11,15 Our data further contributes to the definition of the role of sarcopenia as a possible predictor of reduced survival and cancer treatment toxicity, as has been previously shown in other oncological settings. 10 Accurate measurement tools are also needed in HCC, and CTbased technologies provide measurable and repeatable muscle mass measurement.…”
Section: Discussionmentioning
confidence: 71%
“…This percentage is in line with those observed among HCC cirrhotic patients and in our previous paper in Caucasian patients with HCC using similar L3 SMI thresholds. 11,15 As expected, sarcopenia was linked to gender and age. A paper from Japan previously reported a higher prevalence of sarcopenia in patients treated with sorafenib (close to 65%), probably linked to different thresholds chosen from Asian series published in the literature, and as suggested by the authors, could be unfit for Caucasian patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As HCC patients with complications such as sarcopenia have poor survival rates when compared to HCC patients without sarcopenia, precise determinations of skeletal muscle mass are very important in directing medical care and predicting patient survival. Multifrequency BIA is a simple, non‐invasive, and widely accepted technique for assessing primary sarcopenia .…”
Section: Discussionmentioning
confidence: 99%
“…When we compared the association between Scre, Scys, eGFRcre, eGFRcys, Scre/Scys ratio, and eGFRcre/eGFRcys ratio with HCC patient survival, we found that the eGFRcre/eGFRcys ratio was the best predictor of OS in HCC patients. In general, tumor‐related factors such as tumor stage and tumor markers, and patient‐related factors such as Child–Pugh grade and sarcopenia, are known predictors of survival in HCC patients. In the present study, the tumor‐related factors BCLC stage and AFP were independent predictors in HCC patients, as we expected.…”
Section: Discussionmentioning
confidence: 99%